Strategi Guru Akidah Akhlak dalam Menguatkan Pemahaman Asmaul Husna untuk Menumbuhkan Kesadaran Muraqabah Peserta Didik - Majid, Muhamad Fatkul; Asyrofi, Abdullah Nasihin (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study aims to address the research questions regarding the strategies employed by Akidah Akhlak teachers in strengthening students’ understanding of Asmaul Husna while simultaneously fostering their awareness of muraqabah at MTs Al-Hidayah. The research adopts a qualitative case study approach, using observation, interviews, and documentation as data collection techniques. Data were analyzed through reduction, presentation, and conclusion drawing, supported by source and method triangulation. The findings reveal that Akidah Akhlak teachers implement varied, contextual, and interactive learning strategies that effectively enhance students’ deep comprehension of Asmaul Husna. These approaches also prove successful in cultivating muraqabah awareness by integrating spiritual values into students’ daily lives. Group discussions, reflective activities, and the use of visual media emerge as key components contributing to the success of the learning process. Overall, these strategies significantly support the development of students’ spiritual character and self-control. The study implies that innovative and holistic learning approaches are essential for improving the quality of religious education in schools. Keywords: learning strategies, Asmaul Husna, muraqabah awareness, spiritual character, Islamic religious education.